Isolated Endoscopic Gluteus Medius Repair Can Achieve Successful Clinical Outcomes at Minimum 2-Year Follow-up - Mitchell B. Meghpara, M.D; Mitchell J. Yelton, B.S; Rachel M. Glein, B.S; Mohammad S. Malik, M.D; Philip J. Rosinsky, M.D; Jacob Shapira, M.D; David R. Maldonado, M.D; Hari K. Ankem, M.D; Ajay C. Lall, M.D., M.S; Benjamin G. Domb, M.D (Elsevier, 2021)
Purpose: To report on clinical presentations and outcomes in patients who underwent an isolated endoscopic gluteus medius (GM) repair. Methods: We retrospectively reviewed and prospectively collected data on patients who underwent a primary isolated endoscopic GM repair. Patients were included if the following patient-reported outcome scores were obtained preoperatively and at minimum 2-year follow-up: modified Harris Hip Score (mHHS), Non-arthritic Hip Score (NAHS), and visual analog scale (VAS) score. The minimal clinically important difference (MCID) for the mHHS, NAHS, and Hip Outcome Score-Sports Specific Scale was uniquely calculated for this study. Patients who underwent concomitant procedures including hip arthroplasty and hip arthroscopy were excluded. Results: A total of 26 hips met all inclusion and exclusion criteria, of which 23 hips (88.5%) (22 patients) had a minimum 2-year follow-up. Nineteen hips had a partial-thickness GM tear; 17 (89.5%) were high-grade partial-thickness tears treated with a side-to-side repair through a transtendinous window. Four full-thickness tears with no retraction or fatty infiltration were able to be repaired endoscopically. The mHHS, NAHS, and VAS score all significantly improved (P < .05) from baseline: The mHHS improved from 55.9 to 75.4 (P = .005); the NAHS, from 58.8 to 79.2 (P = .003); and the VAS score, from 5.9 to 3.6 (P = .009). The MCID was calculated for the mHHS, NAHS, and Hip Outcome Score-Sports Specific Scale as 5.8, 7.1, and 11.0, respectively. Most patients achieved the MCID for all 3 patient-reported outcome scores. Conclusions: Appropriately selected patients without concomitant intra-articular hip pathology may achieve successful outcomes at a minimum 2-year follow-up after an isolated endoscopic GM repair. Most isolated endoscopic GM repairs were performed for partial-thickness GM tears. Level of Evidence: Level IV, case-series study.